Yes-Associated Protein 1 Plays Major Roles in Pancreatic Stellate Cell Activation and Fibroinflammatory Responses - Hu, Cheng; Yang, Jiayue; Su, Hsin-Yuan; Waldron, Richard T.; Zhi, Mengmeng; Li, Ling; Xia, Qing; Pandol, Stephen J.; Lugea, Aurelia (Frontiers in Physiology, 2019)
Yes-associated protein 1 (YAP), a transcriptional co-activator and major effector of the Hippo pathway, regulates cell differentiation and morphology in many cell types, and supports aberrant tumor growth. Recent studies showed that YAP is expressed in pancreas tissues in PDAC patients and experimental models of PDAC, with YAP largely found in cancer cells and pancreatic stellate cells (PaSC) in the stroma. Methods & Results: We studied here the role of YAP in the activated phenotype of PaSC. We found that YAP is expressed at low levels in normal mouse pancreas, but protein levels significantly increased after pancreas inflammatory damage induced by repeated cerulein administration in wild-type mice or upon initiation of neoplastic transformation of the pancreas parenchyma in Ptf1-Cre;LSL-KrasG12D/+ (KC) mice. In these animal models, YAP upregulation occurred in parallel with activation and proliferation of PaSC. Consistent with these findings, we found robust YAP expression in culture-activated mouse and human PaSC but not in quiescent, freshly isolated cells. Fully activated PaSC isolated from KC mice or PDAC patient tissues exhibited robust nuclear YAP suggesting YAP transcriptional activity. Agents that induce quiescence such as the Bromodomain and Extra-Terminal (BET) inhibitor iBET151 and the p38 MAPK inhibitor SB203580 reduced YAP levels in PaSC. Stimulation of PaSC with the potent mitogen PDGF elicited marked YAP Ser127 phosphorylation. However, unexpectedly this effect did not diminish YAP nuclear localization, suggesting that YAP phosphorylation at this site does not govern YAP cellular localization in PaSC. siRNA-mediated knockdown of YAP reduced PDGF-induced PaSC expansion in culture and blunted the persistent activation of Akt and ERK elicited by PDGF stimulation, supporting a role for YAP in PDGF-induced cell growth. YAP knockdown also blunted fibro-inflammatory gene expression responses both in unstimulated and TGFβ1-stimulated PaSC. Conclusion: Our data suggest a central role for YAP in sustaining the activated phenotype and fibro-inflammatory responses in PaSC. Moreover, our findings indicate that a complex crosstalk between YAP, TGFβ1 and PDGF pathways regulates PaSC activity and growth.